Entrepreneurial Ecosystem Dynamics in Emerging Economies: A Systematic Literature Review of Innovation, Institutional Gaps, and Digitalization - Nurani, Khadijah; Wardi, Yunia; Rino, Rino (Jurnal Maksipreneur, 2025)
The entrepreneurial ecosystem is a crucial framework for understanding how the interplay of innovation, institutions, and digitalization drives economic growth, especially in emerging economies. However, many developing countries still face structural challenges such as limited access to financing, weak regulatory capacity, and technological gaps that hinder the dynamics of the entrepreneurial ecosystem. These conditions create institutional gaps that impact innovative capabilities and the digital transformation process of entrepreneurship. This study aims to conduct a Systematic Literature Review of various recent empirical and conceptual studies to analyze how innovation, institutional gaps, and digitalization interact in shaping the competitiveness, resilience, and sustainability of the entrepreneurial ecosystem in developing countries. The study's results indicate that the dynamics of the entrepreneurial ecosystem in developing countries are significantly influenced by the strong interactions among innovation, institutions, and digitization. Innovation, especially green and digital innovation, acts as the main driver of value creation and entrepreneurial competitiveness. Institutions serve as the foundation of governance, but still face obstacles in the form of bureaucratic rigidity and policy fragmentation. Meanwhile, digitalization acts as an integrative catalyst that bridges institutional weaknesses, accelerates the flow of information, and strengthens cross-sector collaboration.